2010
DOI: 10.1089/jpm.2009.0388
|View full text |Cite
|
Sign up to set email alerts
|

Directly Observed Patient–Physician Discussions in Palliative and End-of-Life Care: A Systematic Review of the Literature

Abstract: Objectives: To review studies that used direct observation (i.e., videotaping or audiotaping) methods in palliative/end-of-life care communication research. Design: Descriptive thematic analysis. Setting: Multinational studies were conducted in both the outpatient and inpatient setting. Measurements: Extensive bibliographic searches (January 1, 1998 to July 31, 2009) of English-language literature involving physician-patient (or physician-family) interactions were conducted and augmented by reviews of referenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
86
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(89 citation statements)
references
References 34 publications
2
86
1
Order By: Relevance
“…[39][40][41][42][43][44] What our study adds is the insight that parents appreciated receiving this detailed information, as evidenced by their reactions and their questions in return. It may be postulated that the provision of relevant information helps parents to grasp what is happening to their child and regain some feeling of control.…”
Section: Discussionmentioning
confidence: 83%
“…[39][40][41][42][43][44] What our study adds is the insight that parents appreciated receiving this detailed information, as evidenced by their reactions and their questions in return. It may be postulated that the provision of relevant information helps parents to grasp what is happening to their child and regain some feeling of control.…”
Section: Discussionmentioning
confidence: 83%
“…A possible explanation for the absence of this association is that next to the amount of information, the content of information and the way the information is provided are at least equally important for the satisfaction levels of patients with mCRC. 38 Furthermore, patient satisfaction is associated with supportive HCP behaviors 33 ; the way information is provided (although not assessed in this study) could influence the way information will be perceived. 16 Patients with advanced cancer want the HCP to be honest, to convey hope, to speak plain language instead of difficult medical terminology, to be empathic, to give enough time during discussion, and to pace the amount of information to what they can assimilate.…”
Section: Husson Et Al Discussionmentioning
confidence: 92%
“…32 HCPs are inclined to give routine medical/technical information (diagnosis, type of treatment) and avoid emotional and quality-of-life issues. 33 Furthermore, patients with mCRC possibly want (and expect) more direct emotional support from their HCP instead of only a referral to more formal organized support. 32 Our results do not show differences in the perceived level of received information between patients with or without mCRC.…”
Section: Husson Et Al Discussionmentioning
confidence: 99%
“…6 In the intensive care unit setting, a structured case-based curriculum did improve confidence in discussing acute end-of-life issues. 7 Research found that a simple 1-hour education session for ambulatory care improves completion of ACD paperwork, but data are lacking regarding educational interventions for ambulatory residency training.…”
Section: Resultsmentioning
confidence: 99%